Sistem Pembelajaran Bahasa Arab Konsep dan Metodologi dalam Pendidikan Bahasa Asing - Rifai, Ahmad; `Maujud, Fathul (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
Arabic language learning in Indonesia continues to face various challenges, ranging from traditional instructional approaches, limited learning media, and insufficient teacher readiness to develop strategies that meet learners’ needs, thereby requiring a more comprehensive and adaptive learning system aligned with modern educational developments. This study aims to analyze Arabic language learning as an integrated system, identify its key components, and evaluate the methodologies commonly employed. Through an in-depth literature review, the study reveals a shift from conventional methods toward communicative, contextual, integrative, and eclectic approaches that combine multiple strategies to suit learning demands. The use of digital technology, project-based learning, and authentic assessment has begun to enhance learning effectiveness. However, the study also highlights several obstacles, including the lack of authentic learning materials, limited facilities, and variations in teachers’ ability to implement modern approaches. These findings underscore the importance of institutional support, teacher professional development, and collaboration between educators and school environments to build a more adaptive, relevant, and sustainable Arabic language learning system aligned with the demands of 21st-century education.